Peran teknologi informasi dalam mengoptimalkan fungsi public relation di perbankan syariah - Ramadhani, Miagasela Aprilia (Maliki Interdisciplinary Journal, 2024)
The development of information technology has become the key to optimizing the public relations (PR) function in sharia banking. In this context, Islamic banks face unique challenges to build and maintain a good reputation in the eyes of the public. This research aims to explore how information technology, especially social media and digital platforms, can be used to improve communication with customers and the public. Through the use of social media, Islamic banks can convey information in real-time, interact directly with customers, and build a positive image through educational content. However, challenges such as lack of human resources and funding, as well as ethical issues in managing customer data, also need to be addressed. The findings show that Islamic banks that are able to integrate information technology well can increase transparency, customer trust and communication effectiveness. This research is expected to provide insight for Islamic banks in formulating more effective PR strategies.